2017
DOI: 10.1002/glia.23186
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmin‐11 inhibits cytokine secretion and phagocytosis in microglia

Abstract: Cytokine secretion and phagocytosis are key functions of activated microglia. However, the molecular mechanisms underlying their regulation in microglia remain largely unknown. Here, we report that synaptotagmin-11 (Syt11), a non-Ca -binding Syt implicated in Parkinson disease and schizophrenia, inhibits cytokine secretion and phagocytosis in microglia. We found Syt11 expression in microglia in brain slices and primary microglia. Interestingly, Syt11-knockdown (KD) increased cytokine secretion and NO release i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…Syt11 , the encoding gene for Synaptotagmin-11 (Syt11) is contained within a genome wide associated study-identified locus implicated in PD risk [92]. Syt11 localized to the TGN and recycling endosomes and appears to be involved in cytokine secretion and phagocytosis in microglia [93]. Syt11 was recruited to phagosomes and Syt11 deficiency inhibits microglial phagocytosis of α-syn fibrils, supporting its association with PD [93].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Syt11 , the encoding gene for Synaptotagmin-11 (Syt11) is contained within a genome wide associated study-identified locus implicated in PD risk [92]. Syt11 localized to the TGN and recycling endosomes and appears to be involved in cytokine secretion and phagocytosis in microglia [93]. Syt11 was recruited to phagosomes and Syt11 deficiency inhibits microglial phagocytosis of α-syn fibrils, supporting its association with PD [93].…”
Section: Introductionmentioning
confidence: 99%
“…Syt11 localized to the TGN and recycling endosomes and appears to be involved in cytokine secretion and phagocytosis in microglia [93]. Syt11 was recruited to phagosomes and Syt11 deficiency inhibits microglial phagocytosis of α-syn fibrils, supporting its association with PD [93].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have proposed that in the substantia nigra pars compacta, Syt11 is a mediator of neurotoxicity that interacts with Parkin and regulates the pools of dopaminergic vesicles by inhibiting endocytosis (Wang et al 2018). Syt11 has also been proposed to inhibit cytokine secretion and phagocytosis in glia (Du et al 2017), but its precise role in development and function of neural circuits has remained largely unknown. Curiously, constitutive knockout mice lacking Syt4, a close Syt11 homolog, have a normal life span but exhibit enhanced synaptic potentiation and deficits in motor coordination and hippocampus-dependent memory (Ferguson et al 2004;Dean et al 2009).…”
mentioning
confidence: 99%
“…Augurin levels were significantly lower in SAH patients, but we found no significant difference between good and poor outcome patients, nor did we find significant changes with time. Synaptotagmin-11 regulates repair of injured astrocytes following acute brain injury [33] and also suppresses microglial activation under both physiological and pathological conditions, through the inhibition of cytokine secretion and phagocytosis [34]. In this study, synaptotagmin-11 was found to be decreased in good outcome patients compared with healthy controls, but there was no significant difference between the good and poor outcome group.…”
Section: Discussionmentioning
confidence: 60%